Secretory Products in Petals of Centaurea cyanus L. Flowers: A Histochemistry, Ultrastructure, and Phytochemical Study of Volatile Compounds - Aneta Sulborska-Różycka; Elżbieta Weryszko-Chmielewska; Beata Polak; Beata Stefańczyk; Anna Matysik-Woźniak; Robert Rejdak (Molecules, 2022)
(1) Background: Centaurea cyanus L. is a medicinal plant whose flowers are widely used in herbal medicine. The aim of the study was to localise flower tissues that are responsible for the production of secretory products in petals and to analyse the volatile compounds. The volatile compounds of the flowers of this species have not been investigated to date. (2) Methods: Light, fluorescence, scanning and transmission electron microscopy techniques were used in the study. Lipophilic compounds were localised in the tissues using histochemical assays. Volatile compounds were determined with the use of solid phase microextraction (SPME) and gas chromatography-mass spectrometry (GC-MS). (3) Results: The study showed production of secretion in the petal parenchyma, whose ultrastructure has features of a secretory tissue. The lipophilic secretion was localised in the cells and intercellular spaces of the parenchyma and in the walls and surface of epidermal cells, where it accumulated after release through cuticle microchannels. Sesquiterpenes were found to constitute the main group of volatile compounds, with the highest content of β-caryophyllene (26.17%) and α-humulene (9.77%). (4) Conclusions: Given the presence of some volatile components that are often found in resins (caryophyllene, delta-cadinene) and the abundant secretion residues on the epidermal surface, we suppose that the C. cyanus secretion released by the flowers is a resinaceous mixture (oleoresin), which is frequently found in plants, as shown by literature data. This secretion may play an important role in the therapeutic effects of C. cyanus flowers.